Chiral Discrimination of MDPV Enantiomers by Modified 𝛽-Cyclodextrins: Molecular Docking and Semi-Empirical Study - Luckhana Lawtrakul; Suttipong Sutsree; Jakkaphat Kaewmun (Science & Technology Asia, 2025)
In this study, molecular docking and PM7 semiempirical calculations were employed to investigate the binding interactions and enantiorecognition of MDPV enantiomers with various methylated 𝛽-cyclodextrins (BCDs), including heptakis(2-O-methyl)-𝛽 cyclodextrin (2-MEB), heptakis(3-O-methyl)-𝛽-cyclodextrin (3-MEB), heptakis(6-O-methyl)-𝛽-cyclodextrin (6-MEB), and heptakis(2,6-di-O-methyl)-𝛽-cyclodextrin (2,6-DIMEB). The docking simulations revealed three distinct orientations of MDPV within the cyclodextrin cavities, with the methylenedioxy and pyrrolidine rings of MDPV adopting different positions relative to the cyclodextrin rims. The calculated binding free energies (ΔG) indicated that while different orientations slightly affect binding affinity, they do not dramatically influence the stability of the host-guest complexes. Further PM7 calculations confirmed stable 1:1 inclusion complexes, with relative heats of formation (Δ𝑟𝐻) ranging from -41.21 to -92.29 kcal/mol. The methylation of cyclodextrins at specific hydroxyl positions played a crucial role in enhancing enantiorecognition. Notably, 6-MEB, methylated at the narrower primary hydroxyl position, exhibited the most effective enantioseparation, while 2,6-DIMEB, methylated at both rims, showed poor enantiorecognition ability. These findings emphasize the significance of selective methylation in modulating the chiral recognition capabilities of BCD derivatives.